2018
DOI: 10.1016/j.compositesa.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale modeling of the viscoelastic behavior of 3D woven composites

Abstract: A method is presented to predict numerically the homogenized viscoelastic behavior of 3D woven composites using only its constituents' behavior. It is based on elastic homogenizations applied to the Laplace-Carson transform of the time-dependent viscoelastic behavior of the constituents. Two scale chages are necessary: from micro-to meso-scale to obtain the homogenized behavior of the consolidated yarns, and from mesoto macro-scale. The temperature and cure dependent viscoelastic behavior of the matrix is iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 56 publications
0
5
0
3
Order By: Relevance
“…According to the DSC exothermic-time curve as shown in Figure 6, the curing degree curves for different temperatures can be obtained by integrating the time and summarized to obtain. The unitary model of a typical unidirectional FRP was proposed by Adli and Jansen et al, and the method proposed by Saito et al to determine the curing temperature-dependent macroscopic parameters [3][4][5][6][7][8]. The shear modulus is considered almost zero below the gel point but rises rapidly above that point due to the formation of cross-linked structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the DSC exothermic-time curve as shown in Figure 6, the curing degree curves for different temperatures can be obtained by integrating the time and summarized to obtain. The unitary model of a typical unidirectional FRP was proposed by Adli and Jansen et al, and the method proposed by Saito et al to determine the curing temperature-dependent macroscopic parameters [3][4][5][6][7][8]. The shear modulus is considered almost zero below the gel point but rises rapidly above that point due to the formation of cross-linked structures.…”
Section: Resultsmentioning
confidence: 99%
“…The unitary model of a typical unidirectional FRP was proposed by Adli and Jansen et al, and the method proposed by Saito et al to determine the curing temperature-dependent macroscopic parameters [3][4][5][6][7][8]. The shear modulus is considered almost zero below the gel point but rises rapidly above that point due to the formation of cross-linked structures.…”
Section: Resultsmentioning
confidence: 99%
“…O'brien et al 2001Saseendran et al (2016,2017) -- (Meuwissen et al, 2004;Mahnken, 2013) FRP FRP Kravchenko et al, 2016Kravchenko et al, , 2017Yuan et al, 2018(Terada et al, 2013Terada et al, 2014) -FRP FRP Maxwell FRP FRP 2 ( Agius et al, 2016;Hirsekorn et al, 2018)…”
Section: Frpunclassified
“…Seifert et al [ 21 ] studied the time-temperature dependent material properties of 3D braided composite material based on experimental and numerical methods. Hirsekorn et al [ 22 ] obtained the viscoelastic behavior of 3D braided composites from the dependence of component on temperature and degree of cure by a homogenization strategy. Cai et al [ 23 ] reported the thermo-viscoelastic properties of 3D braided composites in different temperature states based on the three-cell model.…”
Section: Introductionmentioning
confidence: 99%